Analisis Pengaruh Nilai Pelanggan,Kualitas Pelayanan Dan Kedekatan Emosional Terhadap Loyalitas Pelanggan (Studi Kasus Pada Pelanggan Hypermart Giant Jl.Mt.Haryono No.146 Malang) - Repiannur Repiannur; N. Rachma; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine and test the effect of the variables examined in this study. The influences tested include, among others, the influence of customer value, service quality, and emotional closeness to customer loyalty. This type of research is quantitative descriptive using an accidental sampling approach. Samples taken were 100 Hypermart Giant customers (Jl.MT.Haryono no.146 Malang). The data collection method used was a questionnaire. Data analysis uses interval analysis. Based on this analysis shows that the customer value variable significantly influences customer loyalty, with a beta coefficient of 4.26, which means that respondents express about customer value (X1) is agree. Variable service quality has a significant effect on customer loyalty, with a beta coefficient of 4.34, which means that respondents expressed about service quality (X2) is agreed. Variable emotional closeness has a significant effect on customer loyalty, with a beta coefficient of 4.23, which means that respondents express emotional closeness (X3) is agreed. Keywords: Customer Value, Service Quality, Emotional Proximity